2019
DOI: 10.1038/s41598-019-43161-2
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogen retention: Comparison of the novel medium cut-off (MCO) membrane with other dialyser membranes

Abstract: Haemodialysis effectively removes small solutes and smaller-sized middle molecules from the blood; however, the clearance of larger middle molecules, which have been associated with negative effects, is poor. The novel medium cut-off (MCO) dialysis membrane has larger pore sizes and a more open structure than other high-flux membranes, providing improved removal of larger middle molecules while retaining albumin. However, larger pore sizes may potentially increase permeability to pyrogens, including endotoxins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Another advantage of the MCO membranes lies in the usage of conventional HD treatment and equipment. These membranes are suitable for using ISO standard dialysis fluid quality and retain endotoxins at a similar level as to other membranes [31]. We performed this expanded dialysis in standard HD modality, using our regular HD equipment and water supply system.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of the MCO membranes lies in the usage of conventional HD treatment and equipment. These membranes are suitable for using ISO standard dialysis fluid quality and retain endotoxins at a similar level as to other membranes [31]. We performed this expanded dialysis in standard HD modality, using our regular HD equipment and water supply system.…”
Section: Discussionmentioning
confidence: 99%
“…The concerns are about an eventual chronic exposure to inflammatory products, such as cytokines, that can be induced by the increased permeability for bacterial degradation products, thus potentially contributing to the micro-inflammatory status of ESRD patients. Two studies have been performed to assess MCO safety related to microbial contamination using in vitro dialysis system [53,54]. Both of them compared LF, HF, MCO and HCO membranes.…”
Section: Microbial Contaminationmentioning
confidence: 99%
“…The mean pore radius is 5 nm, standard deviation 0.1 nm, for the MCO membrane, with a lower variance from the mean, i.e., more uniformity in pore dimension 27 , providing a more selective removal of solutes with reduced albumin leakage. As a comparison, the HCO membrane mean pore radius is 10 nm with a wider standard deviation (2.0 nm) 28 . Kirsch et al observed an albumin loss of 3 g in a four-hour MCO-HD session, which is similar to the loss seen in HF-HDF 17 .…”
Section: Medium Cutoff (Mco)mentioning
confidence: 99%